Evaluasi Proses Penyusunan dan Pengesahan Rancangan Undang-Undang Tindak Pidana Kekerasan Seksual - Patricia, Zefanya; Larasati, Giaby Amanda; Fiandie, Ursula Jacqueline (Media Hukum Indonesia (MHI), 2024)
Sexual violence is a universal issue that cause significant negative impacts on its victims. In addition to deliver impacts on the victim's physical health, sexual violence also leaves a deep traumatic experience. In addition to being contrary to applicable laws and norms, sexual violence is also very contrary to the principles of humanity that are firmly held through human rights. The birth of the Draft of Sexual Violence Crime Law or better known as the RUU TPKS is an important step for Indonesia to strengthen the legal basis for dealing with various forms of sexual violence. Although at the end of its journey the draft has successfully legalized, the long journey of the RUU TPKS reflects the complexity in formulating policies aimed to protect vulnerable groups. This study aims to analyze and reflect the urgency and inhibiting factors in the preparation and ratification of the Draft of Sexual Violence Crime Law.